The tadpole of Allobates sumtuosus (Morales, ‘2000’ 2002) (Anura: Aromobatidae) from its type locality at Reserva Biológica do Rio Trombetas, Pará, Brazil. - Simões, Pedro Ivo; Lima, Albertina P. (Zootaxa, 2012)
Allobates sumtuosus was described by Morales (“2000” [2002]), partially based on individuals collected by R.I. Crombie and R.C. Lynn at Reserva Biológica do Rio Trombetas (REBio Trombetas - Estado do Pará, Brazil). The holotype proceeded from the same locality.